2003
DOI: 10.4049/jimmunol.170.1.635
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy of Autoreactive Th1 and Th2 Cell Responses to Desmoglein 3 in Patients with Pemphigus Vulgaris (PV) and Healthy Carriers of PV-Associated HLA Class II Alleles

Abstract: Pemphigus vulgaris (PV) is the most severe autoimmune bullous skin disorder and is primarily associated with circulating autoantibodies (autoAb) against desmoglein 3 (Dsg3). In light of recent evidence that autoreactive T cells are critical for the induction and regulation of Ab production, the goal of this study was to characterize and quantitate autoreactive T cells in patients with PV and healthy controls. Peripheral Dsg3-reactive Th cells from 28 patients with acute-onset, chronic active, and remittent PV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 39 publications
8
121
0
6
Order By: Relevance
“…Upon selection by MACS cytokine secretion assay, Dsg3-specific Th responses were not only detected in a cohort of PV patients (irrespective of their clinical status) but also in healthy carriers of the PV-associated HLA class II alleles, DRB1*0402 and DQB1*0503. This finding confirms previous studies from our group supporting the idea that carriers of distinct HLA class II alleles are genetically at risk to develop Dsg3-specific T cell responses independent from the development of PV (21,22).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Upon selection by MACS cytokine secretion assay, Dsg3-specific Th responses were not only detected in a cohort of PV patients (irrespective of their clinical status) but also in healthy carriers of the PV-associated HLA class II alleles, DRB1*0402 and DQB1*0503. This finding confirms previous studies from our group supporting the idea that carriers of distinct HLA class II alleles are genetically at risk to develop Dsg3-specific T cell responses independent from the development of PV (21,22).…”
Section: Discussionsupporting
confidence: 82%
“…5). These findings are consistent with epidemiological studies showing a strong association of PV with HLA-DRB1*0402 (16) and HLA-DQB1*0503 (17,18) and a recent study from our group that identified Th cell responses to Dsg3 not only in PV patients but also in healthy carriers of the aforementioned PV-associated HLA class II alleles (22). These findings are in line with three independent studies demonstrating that Dsg3-specific TCC were restricted by HLA-DRB1*0402 (19,20,43).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations